Disaster Education and the Role of Geographers: A Step Toward a Disaster Resilient Ambon City: A Review - Gustavo, Geoffrey John Pascal; Rakuasa, Heinrich (Journal of Education Method and Learning Strategy, 2023)
The alignment of geography concepts in disaster education is an important strategy to build an Ambon City that has high preparedness in facing disaster risks. The integration of geography concepts enables a deeper understanding of geographical factors that influence risk, such as location and topography. This research uses a descriptive Qualitative Method by conducting a literature study. The results show that through disaster education that incorporates aspects of geography, communities can plan appropriate mitigation actions and design disaster-resistant infrastructure. Cross-sector collaboration between the government, private sector, community organizations, and educational institutions is the foundation in dealing with disaster risks in a holistic way. This integrated disaster education builds high awareness of risks and the environment, provides mental and physical preparedness in the face of crisis, and forms a solid foundation for a safer and more resilient future. In the face of disaster threats, integrating geography in disaster education is an important milestone in making Ambon City a city that is ready and resilient in the face of various natural challenges and crises.